THE ROLE OF SOCIAL MEDIA IN THE SPREAD OF RELIGIOUS MODERATION IN THE DIGITAL ERA - Nuha, Nazahah Ulin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research explores the role of social media in the spread of religious moderation in the digital era, with a focus on the Indonesian context. Religious moderation is considered important for maintaining harmony and tolerance in a multicultural society and reducing radicalism and intolerance. Social media, as a broad communication platform, has great potential to spread moderate values and strengthen interfaith dialogue, especially among the younger generation. However, this research also identifies the challenges faced, such as the spread of hoaxes, conflict, and the commodification of religion. To overcome this challenge, proposed strategies include religious moderation education in schools, campaigns on social media, and increasing media literacy. Digital literacy is the key to making positive use of social media, and collaboration between government, educational institutions and society is essential to create a digital environment that supports religious moderation. While there are opportunities to increase awareness and tolerance, challenges from extremist content and misinformation remain, so collective efforts are needed to address these issues.